STRATEGI PENGEMBANGAN USAHATANI NILAM DI KECAMATAN NUHA KABUPATEN LUWU TIMUR - Jusrianto; Rahmawati, Hilda; Khaerati; Ismail, Nurmalasari (Universitas Cokroaminoto Palopo, 2023)
This Research aim was to determine the development strategy of patchouli farming system in Nuha Sub-district. The site of this research was purposively selected with consideration that Nuha sub-district is one of the sub-districts existing in Luwu Timur regency that develops patchouli. Twenty eight respondent samples, 15% of population of patchouli farmers, were selected through simple random sampling method in tree villages. Data were analyzed using SWOT. The SWOT analysis revealed that the farming system was in quadrant I position (support the aggressive strategy) with SO strategy (strengths-opportunities). Program proposed to support the strategy are (1) optimizing land resources in efforts to increase production, 2) utilizing the role of farmer groups in order to develop marketing strategies, 3) empowering the farmers to be better in thinking and acting for any activity implementation, to generate profit in order to increase the productivity and to ensure the production continuity of the farming system, and 4) developing superior local seedlings through government support.